Arabidopsis RAD23B regulates pollen development by mediating degradation of KRP1. (3rd April 2020) - Li, Lan; Li, Bin; Xie, Chong; Zhang, Teng; Borassi, Cecilia; Estevez, José M; Li, Xiushan; Liu, Xuanming
Abstract : The UBL/UBA protein RAD23B plays an important in pollen development by controlling the turnover of the key cell cycle protein, KRP1, as evidenced by defects in the rad23b null mutant. Abstract: The ubiquitin (Ub)/26S proteasome system (UPS) plays a key role in plant growth, development, and survival by directing the turnover of numerous regulatory proteins. In the UPS, the ubiquitin-like (UBL) and ubiquitin-associated (UBA) domains function as hubs for ubiquitin-mediated protein degradation. Radiation sensitive 23 (RAD23), which has been identified as a UBL/UBA protein, contributes to the progression of the cell cycle, stress responses, ER proteolysis, and DNA repair. Here, we report that pollen development is arrested at the microspore stage in a rad23b null mutant. We demonstrate that RAD23B can directly interact with KIP-related protein 1 (KRP1) through its UBL-UBA domains. In addition, plants overexpressing KRP1 have defects in pollen development, which is a phenotype similar to the rad23b mutant. RAD23B promotes the degradation of KRP1 in vivo, which is accumulated following treatment with the proteasome inhibitor MG132. Our results indicate that RAD23B plays an important in pollen development by controlling the turnover of the key cell cycle protein, KRP1.